Penerapan Metode Revitalisasi pada Alih Fungsi Bangunan Pelayanan di Lingkungan Kampus Universitas Riau - Sitompul, Iskandar Romey (Jurnal Ilmiah Global Education, 2025)
Higher education institutions are mandated to provide education, research, and community service in Indonesia. This activity needs cooperation with a lot of people, such as an institute and the public community. Therefore, the university needs to provide adequate public service buildings. Universitas Riau already had a facility for this program. However, the old building's interior not being relevant to recent activity, and because of that, in busy times the situation is not conducive. Under these circumstances, the role of the current study is to emphasize interior design for service buildings based on revitalization method. The final goal is to create interior design for research and community service building at Universitas Riau.